Advances in Phthalocyanine Compounds and their Photochemical and Electro-chemical Properties - Chen, Jun; Zhu, Caijian; Xu, Yong; Zhang, Pengwei; Liang, Tongxiang (Current Organic Chemistry, 2018)
Phthalocyanine, a large ring complex with 18 π electrons, is derived from the abundant porphyrin in nature. In recent years, the phthalocyanine based materials have aroused great interest of scientists, due to their special skeleton structure, which could be screened and assembled by introducing central ions, axial ligands and substituted groups, and thus obtained materials with special physical and chemical stabilities, as well as photochemical, electrochemical, photocatalytic and other functions. In this review, recent advances of phthalocyanine compounds in the field of photochemistry and electrochemistry have been reviewed and summarized. Firstly, progress in photochemical properties was introduced, including research and ideas of optical limiting properties, photocatalysis and photodynamic therapy. The existing problems and future research directions of phthalocyanine compounds based on photochemical applications are summarized and analyzed. Secondly, the phthalocyanine compounds as electrode materials for lithium ion batteries were introduced. The modification idea, energy storage mechanism, the existing problems and future research directions of phthalocyanine compounds as energy storage materials are summarized and analyzed. The structural diversity and adjustable properties of phthalocyanine based material make it special optical, electrical and magnetic material, which can provide theoretical guidance for the design of large ring conjugated photoelectric functional materials with excellent performance.
Keywords: Phthalocyanine